Development of a mechanism for managing the level of investment in R&D of city-forming enterprises (by the example of the metallurgical industry) - Yessengaliyeva, Saltanat; Tapalova, Assel; Melekova, Assel; Ibadildin, Nurkhat; Kairliyeva, Gaukhar; Serikbayev, Serik; Nursapina, Kanbibi (Eastern-European Journal of Enterprise Technologies, 2024)
The object of the study is investment in R&D of enterprises. The problem of developing a mechanism for managing the level of R&D investment at industrial enterprises has been solved. The results are obtained: – gradation of R&D investment levels at enterprises based on the application of the beta coefficient calculation methodology adapted to the R&D sphere; – distribution of city-forming enterprises of the metallurgical industry by R&D investment levels: high level – 27 % of surveyed enterprises, average – 18 %, low – 55 %, critical – 0 %; – development of a matrix based on the comparison of the level of R&D investment and the level of sales volumes of the enterprise’s products calculated according to one algorithm. For each cell of the matrix, management decisions of strategic nature are proposed to increase the level of R&D investment. The results obtained are explained by the assumption of a linear relationship between the size of R&D investment of a particular enterprise over time and aggregate industry R&D investment (as a benchmark). The tendency of R&D investment growth in the industry, regularity of R&D investments of the surveyed enterprises were confirmed, time series of R&D investment both at the evaluated enterprise and in the industry as a whole were processed using trend smoothing. The features of the obtained results lie in the application of comparable coefficients (investments in R&D), as well as in the application of the developed assessment in the management of the enterprise. The practical significance of this study results is the possibility of applying the obtained conclusions and recommendations to increase the level of R&D investment of large industrial enterprises in the volume, scope and conditions corresponding to the developing economy